Thermocline Dynamics and Nitrogen Cycling Drive Productivity Shifts in the South China Sea Across Glacial Cycles - Li‐Wei Zheng; Hongbao Qu (Geophysical Research Letters)
Abstract The South China Sea (SCS) nitrogen cycle responds dynamically to glacial–interglacial climate changes, yet the drivers of nitrogen isotope variability remain debated. We present a synthesis of foraminifera‐bound δ15N (FB‐δ15N) records, together with complementary organic and amino‐acid δ15N data from across the SCS. In the eastern and northern SCS, FB‐δ15N peaks during glacials when intensified East Asian Winter Monsoons shoal the thermocline, enhance upwelling of 15N‐enriched deep nitrate, and stimulate export production. Conversely, western and southern SCS records exhibit δ15N minima during interglacials, reflecting enhanced nitrogen fixation and/or partial nitrate utilization. This east–west divergence highlights the important role of upper‐ocean structure in modulating nitrogen isotopes, alongside potential sea‐level–driven nutrient effects. Our results establish FB‐δ15N as a sensitive proxy for reconstructing nutrient dynamics and monsoon‐driven upwelling in marginal seas and underscore the influence of thermocline variability in shaping marine nitrogen cycling over glacial cycles.